Construction of virtual environments through integration of three dimensional (3D) objects / Mohd Fauzi Mustafa - Mohd Fauzi, Mustafa (2004)
Annually, all the undergraduates of Faculty of Computer Science and Information Technology, University of Malaya are required to prepare a final project as part of the degree requirement. It is hoped that the student will be apply concepts learned in the university into the production of the project. For my final project, I have chosen to do a study and design of a three-dimensional (3D) integration tool which able to integrate 3D objects into the virtual environment. This is a group project that develops a tool which is user-friendly and suitable for user who always desire to integrate 3D objects in a single virtual environment and to perform transformation to 3D objects accordingly to their needs. The user will be able to integrate 3D objects from the provided 3D objects by the tool or import it from other sources. After integration the user will be able to perform transformation such as rotation, scaling and rotation to the 3D objects within the virtual environment. With this function, the user will be able to arrange the location, siza and view of their 3D objects according to their needs and desires. The Waterfall Model with Prototyping approach was selected for the development process because the strength of both the Waterfall Model and Prototyping can be combined in a single project and reduces the risk involved. The programming languages that used to develop the tool are Microsoft Visual C++, Visual Basic.net, OpenGL and Microsoft Windows XP has been chosen as the operating system.